DEEP SCAFFOLDING BASED ON RME TO REDUCE SLOW LEARNERS’ ERRORS IN NUMERACY PROBLEM SOLVING - Kadek Adi Wibawa; I Made Dharma Atmaja; I Gde Dhika Widarnandana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Slow learners often struggle with understanding problem contexts, constructing representations, and applying appropriate strategies due to limitations in working memory, processing speed, and conceptual generalization. Therefore, structured, gradual, meaningful and enjoyable assistance is needed which is linked to the experiences and lives around slow learners students, which is called deep scaffolding based on Realistic Mathematics Education (RME). This study aims to explore the implementation of Deep Scaffolding based on RME to reduce thinking errors among slow learner students in numeracy problem solving. An interpretative qualitative method with an exploratory single-case study design was employed to gain an in-depth understanding of the cognitive and affective learning processes of one selected slow learner student. Data were collected through contextual numeracy worksheets, direct observation, and semi-structured interviews guided by the mindful–meaningful–joyful scaffolding framework. The findings reveal that deep scaffolding based on RME effectively improved the student’s ability to interpret contexts, build accurate visual representations, apply basic arithmetic strategies, and evaluate multiple solution alternatives. SL1 demonstrated significant growth in conceptual understanding and problem-solving flexibility, alongside increased confidence, motivation, and positive emotional engagement. These results indicate that deep scaffolding integrated with RME provides meaningful cognitive and affective support for slow learners in numeracy learning. This study recommends that teachers in inclusive classrooms apply structured deep scaffolding and contextual task to enhance comprehension and problem-solving accuracy among slow learners.